Hematological Studies on Malnad Gidda Breed of Cattle in Karnataka - Narynaswamy, Gowda M; Veena, T; Krishnaswamy, A; Nagaraja, CS; Sridhar, NB; Ganesh, K; kalmath, GP (Indian Journal of Veterinary Sciences and Biotechnology, 2017)
The present study was conducted to establish the base line hematological values in Malnad Gidda cattle during winter and summer seasons under the agro-climatic condition of Western Ghats of Karnataka. Thirty healthy Malnad Gidda cattle divided into five groups based on age, sex and lactation. The mean values of TEC, Hb, PCV, ESR, TLC and eosinophil per cent were significantly (P